Sustainable leachate treatment by integrating electrolysis with palm-shell activated carbon contactor for environmental protection - Ahsan, Amimul; Mat Ali, Muhamad Jasarudin Bin; Rashid, Md. Redowan; Kabir, Mozaher Ul; Shafiquzzaman, Md.; Imteaz, Monzur; Idrus, Syazwani; Aljaradin, Mohammad; Alresheedi, Mohammad T. (Nature Research, 2025)
The increasingly concerning issue of water pollution caused by untreated leachate necessitates the implementation of effective wastewater treatment methods. This study addresses the crucial issue of landfill leachate treatment through an innovative and environmentally friendly approach that integrates electrolysis with palm-shell activated carbon contactors. The efficacy of an integrated process for pollutants removal was assessed involving electrolysis with aluminum and iron electrodes, activated carbon contactors with varying bed depths, and the influence of salinity. The findings of the study demonstrated significant advancements in the removal of pollutants from landfill leachate. The utilization of aluminum and iron electrodes in electrolysis has exhibited enhanced efficacy in the removal of several parameters, including ammonia nitrogen, total suspended solids (TSS), chemical oxygen demand (COD) and biochemical oxygen demand (BOD). The pollutants removal efficiency was further improved by implementing up-flow activated carbon treatment, with a bed depth of 15 cm yielding most favorable outcomes. Additionally, the investigation explored the impact of salinity on the efficacy of pollutants removal. Except for BOD, which demonstrated good removal efficiency even at 5% salt, results indicated that the removal effectiveness was maximum when no salt was applied to the samples. The results suggest that this integrated method offers a sustainable and effective solution for landfill leachate treatment, potentially leading to better water quality and environmental preservation. Future study should focus on implementing rigorous laboratory protocols, ensuring accurate dilution factors, refraining from reusing activated carbon, maintaining continuous monitoring throughout treatment operations, and investigating alternative treatment approaches. This study makes a valuable contribution to the ongoing endeavors aimed at tackling the environmental issues related to the treatment of landfill leachate.